1974
DOI: 10.1246/bcsj.47.813
|View full text |Cite
|
Sign up to set email alerts
|

Standard Potentials of Alkali Metals, Silver, and Thallium Metal/Ion Couples in N,N′-Dimethylformamide, Dimethyl Sulfoxide, and Propylene Carbonate

Abstract: The relative standard potentials of alkali metals, silver, and thallium metal/ion couples in N,N′-dimethylforrnamide(DMF), dimethyl sulfoxide(DMSO), and propylene carbonate (PC) were measured against an aqueous saturated calomel electrode(SGE). These standard potentials of lithium, sodium, potassium, rubidium, caesium, thallium, and silver are −3.237, −2.898, −3.116, −3.079, −3.079, −0.643, and +0.372 V vs. SGE respectively in DMSO, and −3.163, −2.830, −3.067, −3.040, −3.048, −0.559, and +0.538 V vs. SGE respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…It is noteworthy that the discharge potentials of 3.9 and 3.2 V of K x FeFe-PW are higher than those of Na x FeFe-PW, 3.3 and 3.0 V, in Na-ion batteries [29]. This may have to do with the facts that the standard potential of K + /K is ~0.3 V lower than that of Na + /Na in PC solvent [31] and that the Gibbs free energy may be lower when K-ions are incorporated into the FeFe(CN) 6 framework [32]. The first-cycle charge/discharge capacity of 105.1/110.5 mAh g -1 for FeFe-PW gives rise to an initial coulombic efficiency of 105.1%, which is likely due to the mixed oxidation states of Fe (II) and Fe (III) of the iron site coordinated to nitrogen end of cyanide, thus resulting in a shorter low-potential plateau during depotassiation [29].…”
Section: Methodsmentioning
confidence: 93%
“…It is noteworthy that the discharge potentials of 3.9 and 3.2 V of K x FeFe-PW are higher than those of Na x FeFe-PW, 3.3 and 3.0 V, in Na-ion batteries [29]. This may have to do with the facts that the standard potential of K + /K is ~0.3 V lower than that of Na + /Na in PC solvent [31] and that the Gibbs free energy may be lower when K-ions are incorporated into the FeFe(CN) 6 framework [32]. The first-cycle charge/discharge capacity of 105.1/110.5 mAh g -1 for FeFe-PW gives rise to an initial coulombic efficiency of 105.1%, which is likely due to the mixed oxidation states of Fe (II) and Fe (III) of the iron site coordinated to nitrogen end of cyanide, thus resulting in a shorter low-potential plateau during depotassiation [29].…”
Section: Methodsmentioning
confidence: 93%
“…Particularly in propylene carbonate (PC), the value is -0.09 V vs. Li ? /Li [15][16][17]. Furthermore, the natural abundance of potassium is comparable to that of sodium [18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to this, the KIB technology can benefit from the lowest potential for K + /K redox couple in some organic electrolytes . For instance, even though the standard electrode potential versus SHE of K + /K (−2.936 V) is in between Li + /Li (−3.040 V) and Na + /Na (−2.714 V) couples, the theoretical and practical calculations, however, demonstrated that the K + /K (−2.88 V) redox couple could exhibit lowest reduction potential in organic solvents like propylene carbonate (PC) as compared to Li + /Li (≈2.79 V) and Na + /Na (≈2.56 V) . This could lead to a wider potential window, resulting into high energy density for KIBs.…”
Section: Introductionmentioning
confidence: 99%